Pengaruh Kualitas Sosialisasi dan Pelatihan terhadap Minat Bekerja ke Luar Negeri bagi Peserta Program SIPERANTAU (Studi Kasus BP3MI Sumatera Barat) - Sri Muhajir; Afriyeni Afriyeni (Lembaga Yasin AlSys, 2026)
The high interest among the people of West Sumatra in working abroad is influenced by economic motives and the cultural value of merantau, while studies on the influence of dissemination quality and training on interest in working abroad through the SIPERANTAU Program remain limited. This study aimed to analyze the influence of dissemination quality and training on interest in working abroad among participants of the SIPERANTAU Program at BP3MI West Sumatra, both partially and simultaneously. This study used a quantitative approach with an associative survey design. The research sample consisted of 154 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS. The results showed that dissemination quality had a positive and significant effect on interest in working abroad, with a t-statistic of 10.988 and a significance value of 0.000. Training also had a positive and significant effect, with a t-statistic of 3.870 and a significance value of 0.000. Simultaneously, dissemination quality and training had a significant effect on interest in working abroad, with an F-statistic of 84.865 and a significance value of 0.000. The Adjusted R Square value of 0.523 indicates that the two variables contributed 52.3%. The conclusion of this study confirms that dissemination quality and training play an important role in increasing SIPERANTAU Program participants’ interest in working abroad. The implications of this study emphasize the importance of synergy between information and training in promoting legal, competent, and protected labor migration.